PENGARUH PENDIDIKAN DAN PELATIHAN STRUKTURAL TERHADAP KOMPETENSI KEPEMIMPINAN APARATUR SIPIL NEGARA STUDI DI SEKRETARIAT DAERAH KOTA BITUNG - ASTRA, FADILLA; Mandey, Jantje; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: Education and training aims to provide an opportunity to improve the skills and personnel in theirskills, especially in areas related to leadership or managerial required in the achievement of the objectives ofthe organization. In fact the structural Training is not given to most of the ASN in Bitung cityareas Secretariat, thus causing some structural position of Echelon IIIand IV Echelon structural position still held by the ASN which has yet to meet the requirementsof appropriate structural level Training position. These conditions cancause structural officials leadership competencies to be weak or insufficient. Based on the issue of thepurpose of this research is to find out and measure the influence of the education and training of leadershipcompetencies to increased structural apparatus of the civil State in the Secretariat of the Regional City ofBitung.This research is exploratory research method. This usage of the intent to address education andtraining Are a structural effect on the competence of the leadershipof the Civil State Apparatus in Bitung city areas Secretariatâ€The results showed significant relationships had a structural Training againstthe leadership competencies ASN in the Secretariat City of Bitung. It is seen from the value of the correlationR = 0.86 turns approaching the maximum value of the correlation coefficient (1.00), and the value of thecoefficient of determination (R-square) of 0.74 has significance that the development/enhancement ofleadership competence ASN in Bitung City Area is the Secretariat of 74 or 0.74% determined/ influencedby variable structural Training, while the rest amounted to 26% specified/ influenced by other variables.This means that the higher the structural Training undertaken/ gainedASN then the higher leadership competencies from the ASN concerned. Structural determinationof power have training/ significant deciding against the leadership competencies ASN in theSecretariat City of Bitung. This means that the level of competence of the leadership of the ASN issignificantly influenced by structural Training followed/retrieved. Training structural influence on attitudesand behavior of the ASN in carrying out the duties of their Office.Keywords: education and training, structural, competence, leadership, Civil State Apparatus (ASN)